Keluarga 69 - P. Ramlee, Tan Sri, 1929-1973
Bakar, a wealthy but short-tempered man, throws his happy-go-lucky son, Osman, out of the house because of his playboy behavior. Osman takes shelter with his friend, Badim, until they are both evicted by their landlord -- none other than Bakar himself. The two homeless friends join a traveling stage troupe. Soon Osman discovers a singing career and is offered a recording contract. But he discovers that he has been tricked and falls into despair. A secret love, Siti, arrives just in time to stop him from putting an end to his life. Osman marries Siti, then decides to bring her home to meet his father. But meanwhile Bakar has married Minah, who is Siti's daughter from a previous marriage. To further complicate the family relationship, Abu (Minah's father, and Siti's ex-husband), who is now Bakar's servant, marries Bakar's ex-wife, Osman's motherdiscovers a singing career and is offered a recording contract. But he discovers that he has been tricked and falls into despair. A secret love, Siti, arrives just in time to stop him from putting an end to his life. Osman marries Siti, then decides to bring her home to meet his father. But meanwhile Bakar has married Minah, who is Siti's daughter from a previous marriage. To further complicate the family relationship, Abu (Minah's father, and Siti's ex-husband), who is now Bakar's servant, marries Bakar's ex-wife, Osman's mother.